Skip to main content
\(\require{cancel}\newcommand{\abs}[1]{\left\lvert#1\right\rvert} \newcommand{\point}[2]{\left(#1,#2\right)} \newcommand{\highlight}[1]{{\color{blue}{{#1}}}} \newcommand{\highlightr}[1]{{\color{red}{{#1}}}} \newcommand{\highlightg}[1]{{\color{green}{{#1}}}} \newcommand{\highlightp}[1]{{\color{purple}{{#1}}}} \newcommand{\highlightb}[1]{{\color{brown}{{#1}}}} \newcommand{\lowlight}[1]{{\color{lightgray}{#1}}} \newcommand{\attention}[1]{\mathord{\overset{\downarrow}{#1}}} \newcommand{\substitute}[1]{{\color{blue}{{#1}}}} \newcommand{\addright}[1]{{\color{blue}{{{}+#1}}}} \newcommand{\addleft}[1]{{\color{blue}{{#1+{}}}}} \newcommand{\subtractright}[1]{{\color{blue}{{{}-#1}}}} \newcommand{\multiplyright}[2][\cdot]{{\color{blue}{{{}#1#2}}}} \newcommand{\multiplyleft}[2][\cdot]{{\color{blue}{{#2#1{}}}}} \newcommand{\divideunder}[2]{\frac{#1}{{\color{blue}{{#2}}}}} \newcommand{\divideright}[1]{{\color{blue}{{{}\div#1}}}} \newcommand{\apple}{\text{šŸŽ}} \newcommand{\banana}{\text{šŸŒ}} \newcommand{\pear}{\text{šŸ}} \newcommand{\cat}{\text{šŸ±}} \newcommand{\dog}{\text{šŸ¶}} \newcommand{\lt}{<} \newcommand{\gt}{>} \newcommand{\amp}{&} \)

Section1.15Functions

Subsection1.15.1Written Examples

When solving inequalities involving functions that are presented in graphical form, we follow a two-step process. We first use the function to identify the points on the curve whose \(-y\)-coordinates satisfy the property implied by the inequality statement. We then identify the \(x\)-coordinates of those points, which collectively make up the solution set to the inequality.

In FigureĀ 1.15.1, I've indicated all of the points on the function named \(g\) that have \(y\)-coordinates greater than or equal to \(1\text{.}\) I've also marked off the portion of the \(x\)-axis over which these points lie. Since the \(y\)-coordinates of the points are the values of \(g(x)\text{,}\) we can infer from this that the solution set to the inequality \(g(x) \geq 1\) is \([-4.5,3]\text{.}\)

plain text
Figure1.15.1\(y=g(x)\)

In FigureĀ 1.15.2, I've indicated all of the points on the function named \(g\) that have \(y\)-coordinates less than to \(44\text{.}\) I've also marked off the portion of the \(x\)-axis over which these points lie. Since the \(y\)-coordinates of the points are the values of \(g(x)\text{,}\) we can infer from this that the solution set to the inequality \(g(x) \lt 4\) is \((-\infty,-3) \cup (0,6]\text{.}\)

plain text
Figure1.15.2\(y=g(x)\)

Subsection1.15.2Practice Exercises (with step-by-step solutions)

Problem Set 1

Determine each of the stated function values.

  1. Determine \(g(7)\) where \(g(t)=8-4t\text{.}\)
  2. Determine \(f(-3)\) where \(f(x)=-x^2+5x+12\text{.}\)
  3. Determine \(h(33)\) where \(h(x)=-\sqrt{\frac{x-25}{2}}\text{.}\)
  4. Determine \(t(22)\) where \(t(x)=17\text{.}\)
  5. Determine \(y(-6)\) where \(y(t)=\abs{-9-t}+3\text{.}\)
  6. Determine \(z(-1)\) where \(z(x)=\frac{x+6}{x^2+1}\text{.}\)
  7. Determine \(k(4)\) where \(k(t)=3\sqrt{21-t^2}\text{.}\)

Problem Set 2

Determine the solution set for each of the following equations.

  1. Solve \(f(x)=12\) where \(f(x)=4-x\text{.}\)
  2. Solve \(h(t)=100\) where \(h(t)=t^2-21\text{.}\)
  3. Solve \(p(x)=-14\) where \(p(x)=6-\abs{x}\text{.}\)
  4. Solve \(w(y)=10\) where \(w(y)=y^2-y-2\text{.}\)
  5. Solve \(r(t)=s(t)\) where \(r(t)=\frac{5}{7}t-3\) and \(s(t)=\frac{2}{3}t+\frac{11}{21}\text{.}\)
  6. Solve \(g(x)=y(x)\) where \(q(x)=6-4x^2\) and \(y(x)=(3-x)(8+4x)\text{.}\)

Problem set 3

Determine each of the following function values based upon the function \(f\) shown in FigureĀ 1.15.3.

  1. \(f(4)\)
  2. \(f(2)\)
  3. \(f(5)\)
  4. \(f(1)\)

Determine the solution set to each of the following equations based upon the function \(f\) shown in FigureĀ 1.15.3.

  1. \(f(x)=-1\)
  2. \(f(x)=2\)
  3. \(f(x)=-3\)
  4. \(f(x)=5\)
plain text
Figure1.15.3\(y=f(x)\)

Problem Set 4

Determine each of the following function values based upon the function \(g\) shown in FigureĀ 1.15.4.

  1. \(g(-1)\)
  2. \(g(2)\)
  3. \(g(6)\)
  4. \(g(-6)\)

Determine the solution set to each of the following equations based upon the function \(g\) shown in FigureĀ 1.15.4.

  1. \(g(x)=-2\)
  2. \(g(x)=3\)
  3. \(g(x)=-6\)
  4. \(g(x)=-10\)
plain text
Figure1.15.4\(y=g(x)\)

Problem Set 5

Determine each of the following function values based upon the function \(k\) shown in FigureĀ 1.15.5.

  1. \(k(2)\)
  2. \(k(0)\)
  3. \(k(4)\)
  4. \(k(-3)\)

Determine the solution set to each of the following equations based upon the function \(k\) shown in FigureĀ 1.15.5.

  1. \(k(x)=1\)
  2. \(k(x)=4\)
  3. \(k(x)=5\)
  4. \(k(x)=6\)

plain text
Figure1.15.5\(y=k(x)\)
Solution

Problem Set 1

  1. \(\begin{aligned}[t] g(\highlight{7})\amp=8-4(\highlight{7})\\ \amp=8-28\\ \amp=-20 \end{aligned}\)
  2. \(\begin{aligned}[t] f(\highlight{-3})\amp=-(\highlight{-3})^2+5(\highlight{-3})+12\\ \amp=-9-15+12\\ \amp=-12 \end{aligned}\)
  3. \(\begin{aligned}[t] h(\highlight{33})\amp=-\sqrt{\frac{\highlight{33}-25}{2}}\\ \amp=-\sqrt{\frac{8}{2}}\\ \amp=-\sqrt{4}\\ \amp=-2 \end{aligned}\)
  4. \(\begin{aligned}[t] t(\highlight{22})\amp=17\\ \end{aligned}\)
  5. \(\begin{aligned}[t] y(\highlight{-6})\amp=\abs{-9-(\highlight{-6})}+3\\ \amp=\abs{-3}+3\\ \amp=3+3\\ \amp=6 \end{aligned}\)
  6. \(\begin{aligned}[t] z(\highlight{-1})\amp=\frac{\highlight{-1}+6}{(\highlight{-1})^2+1}\\ \amp=\frac{5}{2} \end{aligned}\)
  7. \(\begin{aligned}[t] k(\highlight{4})\amp=3\sqrt{21-\highlight{4}^2}\\ \amp=3\sqrt{21-16}\\ \amp=3\sqrt{5} \end{aligned}\)

Problem Set 2

  1. Solve \(f(x)=12\) where \(f(x)=4-x\text{.}\)
    \begin{align*} f(x)\amp=12\\ 4-x\amp=12\\ 4-x\subtractright{4}\amp=12\subtractright{4}\\ -x\amp=8\\ \multiplyleft{-1}-x\amp=\multiplyleft{-1}8\\ x\amp=-8 \end{align*}
    The solution set is \(\{-8\}\text{.}\)
  2. Solve \(h(t)=100\) where \(h(t)=t^2-21\text{.}\)
    \begin{align*} h(t)\amp=100\\ t^2-21\amp=100\\ t^2-21\addright{21}\amp=100\addright{21}\\ t^2\amp=121\\ t\amp=\pm\sqrt{121}\\ t\amp=\pm 11 \end{align*}
    The solution set is \(\{-11,11\}\text{.}\)
  3. Solve \(p(x)=-14\) where \(p(x)=6-\abs{x}\text{.}\)
    \begin{align*} p(x)\amp=-14\\ 6-\abs{x}\amp=-14\\ 6-\abs{x}\subtractright{6}\amp=-14\subtractright{6}\\ -\abs{x}\amp=-20\\ \multiplyleft{-1}-\abs{x}\amp=\multiplyleft{-1}-20\\ \abs{x}\amp=20\\ x\amp=\pm 20 \end{align*}
    The solution set is \(\{-20,20\}\text{.}\)
  4. Solve \(w(y)=10\) where \(w(y)=y^2-y-2\text{.}\)
    \begin{align*} w(y)\amp=10\\ y^2-y-2\amp=10\\ y^2-y-2\subtractright{10}\amp=10\subtractright{10}\\ y^2-y-12\amp=0\\ (y-4)(y+3)\amp=0 \end{align*}
    \begin{align*} y-4\amp=0\amp\amp\text{ or }\amp y+3\amp=0\\ y-4\addright{4}\amp=0\addright{4}\amp\amp\text{ or }\amp y+3\subtractright{3}\amp=0\subtractright{3}\\ y\amp=4\amp\amp\text{ or }\amp y\amp=-3 \end{align*}
    The solution set is \(\{-3,4\}\text{.}\)
  5. Solve \(r(t)=s(t)\) where \(r(t)=\frac{5}{7}t-3\) and \(s(t)=\frac{2}{3}t+\frac{11}{21}\text{.}\)
    \begin{align*} r(t)\amp=s(t)\\ \frac{5}{7}t-3\amp=\frac{2}{3}t+\frac{11}{21}\\ \multiplyleft{21}(\frac{5}{7}t-3)\amp=\multiplyleft{21}(\frac{2}{3}t+\frac{11}{21})\\ 15t-63\amp=14t+11\\ 15t-63\addright{63}\amp=14t+11\addright{63}\\ 15t\amp=14t+74\\ 15t\subtractright{14t}\amp=14t+74\subtractright{14t}\\ t\amp=74 \end{align*}
    The solution set is \(\{74\}\text{.}\)
  6. Solve \(g(x)=y(x)\) where \(q(x)=6-4x^2\) and \(y(x)=(3-x)(8+4x)\text{.}\)
    \begin{align*} g(x)\amp=y(x)\\ 6-4x^2\amp=(3-x)(8+4x)\\ 6-4x^2\amp=24+4x-4x^2\\ 6-4x^2\addright{4x^2}\amp=24+4x-4x^2\addright{4x^2}\\ 6\amp=24+4x\\ 6\subtractright{24}\amp=24+4x\subtractright{24}\\ -18\amp=4x\\ \divideunder{-18}{4}\amp=\divideunder{4x}{4}\\ -\frac{9}{2}\amp=x \end{align*}
    The solution set is \(\{-\frac{9}{2}\}\text{.}\)

Problem Set 3

  1. \(f(4)=2\)
  2. \(f(2)=2\)
  3. \(f(5)\) is not defined.
  4. \(f(1)=5\)
  1. The solution set is \(\{-1,3\}\text{.}\)
  2. The solution set is \(\{-4,-2,0,2,4\}\text{.}\)
  3. The solution set is \(\emptyset\text{.}\)
  4. The solution set is \(\{-3,1\}\)

Problem Set 4

  1. \(g(-1)=6\)
  2. \(g(2)=0\)
  3. \(g(6)=-8\)
  4. \(g(-6)\) is not defined.
  1. The solution set is \(\{-2,3\}\text{.}\)
  2. The solution set is \(\{\frac{1}{2}\}\text{.}\)
  3. The solution set is \(\{-4,5\}\)
  4. The solution set is \(\{7\}\text{.}\)

Problem Set 5

  1. \(k(2)\) is undefined.
  2. \(k(0)-3\)
  3. \(k(4)=4\)
  4. \(k(-3)=-5\)
  1. The solution set is \(\{-1,5\}\text{.}\)
  2. The solution set is \(\{4\}\text{.}\)
  3. The solution set is \(\{3\}\text{.}\)
  4. The solution set is \(\emptyset\text{.}\)

Problem 1

Determine the domain of each of the following functions. Where possible, state the domain using interval notation.

  1. \(y(x)=\sqrt{15-x}\)
  2. \(f(t)=\sqrt[3]{t^2-9}\)
  3. \(w(x)=\frac{x-7}{x-12}\)
  4. \(g(x)=\frac{x+3}{x^2+8x+15}\)
  5. \(r(t)=t^2-3t+9\)
  6. \(k(t)=\frac{t^2+16}{t^2+16}\)

Problem 2

Determine the domain and range of the function \(f\) shown in FigureĀ 1.15.6. State the domain and range using interval notation.

plain text
Figure1.15.6\(y=f(x)\)

Problem 3

Determine the domain and range of the function \(g\) shown in FigureĀ 1.15.7. State the domain and range using interval notation.

plain text
Figure1.15.7\(y=g(x)\)

Problem 4

Determine the domain and range of the function \(k\) shown in FigureĀ 1.15.11. State the domain and range using interval notation.

plain text
Figure1.15.8\(y=k(x)\)

Solution

Problem 1

  1. To determine the domain of \(y(x)=\sqrt{15-x}\text{,}\) we begin by noting that we cannot take the square root of a negative number (at least over the real numbers). This gives us the following.

    \begin{align*} 15-x \amp\ge 0\\ 15-x\subtractright{15} \amp\ge 0\subtractright{15}\\ -x \amp\ge -15\\ \multiplyleft{-1}-x \amp\le \multiplyleft{-1}-15\\ x \amp\le 15 \end{align*}

    The domain of \(y\) is \((-\infty,15)\)

  2. To determine the domain of \(f(t)=\sqrt[3]{t^2-9}\text{,}\) we begin by noting that the polynomial expression \(t^2-9\) is defined for all real numbers as is the cube root function. So the domain of \(f\) is \((-\infty,\infty)\text{.}\)

  3. To determine the domain of \(w(x)=\frac{x-7}{x-12}\text{,}\) we begin by noting that we cannot divide by zero. This gives us the following.

    \begin{align*} x-12 \amp\ne 0\\ x-12\addright{12} \amp\ne 0\addright{12}\\ x \amp\ne 12 \end{align*}

    The domain of \(w\) is \((-\infty,12) \cup (12,\infty)\text{.}\)

  4. To determine the domain of \(g(x)=\frac{x+3}{x^2+8x+15}\text{,}\) we begin by noting that we cannot divide by zero. This gives us the following.

    \begin{align*} x^2+8x+15 \amp\ne 0\\ (x+3)(x+5) \amp\ne 0 \end{align*}
    \begin{align*} x+3 \amp\ne 0 \amp\amp\text{ and }\amp x+5 \amp\ne 0\\ x+3\subtractright{3} \amp\ne 0\subtractright{3} \amp\amp\text{ and }\amp x+5\subtractright{5} \amp\ne 0\subtractright{5}\\ x \amp\ne -3 \amp\amp\text{ and }\amp x \amp\ne -5 \end{align*}

    The domain of \(g\) is \((-\infty,-5) \cup (-5,-3) \cup (-3,\infty)\text{.}\)

  5. To determine the domain of \(r(t)=t^2-3t+9\text{,}\) we begin by noting that \(r\) is a polynomial function and polynomial functions are defined for all real numbers. So the domain of \(r\) is \((-\infty,\infty)\text{.}\)

  6. To determine the domain of \(k(t)=\frac{t^2+16}{t^2+16}\text{,}\) we begin by noting that we cannot divide by zero. But \(t^2+16\) is positive for all real number values of \(t\text{,}\) so no value of \(t\) will cause division by zero. So the domain of \(k\) is \((-\infty,\infty)\text{.}\)

Problem 2

The domain is \([-4,5),\text{.}\) The range is \([-1,5]\text{.}\)

plain text
Figure1.15.9\(y=f(x)\)

Problem 3

The domain is \((-6,\infty)\text{.}\) The range is \((-\infty,6]\text{.}\)

plain text
Figure1.15.10\(y=g(x)\)

Problem 4

The domain is \((-\infty,0] \cup (2,\infty)\text{.}\) The range is \((-\infty,6]\text{.}\)

plain text
Figure1.15.11\(y=k(x)\)

  1. Simplify \(f(x-7)\) for the function \(f(x)=3x+12\text{.}\)
  2. Simplify \(g(x)+9\) for the function \(g(x)=14-7x\text{.}\)
  3. Simplify \(h(5-2t)\) for the function \(h(t)=\sqrt{3-t^2}\text{.}\)
  4. Simplify \(k(x+4)+3\) for the function \(k(x)=2x^2-3\text{.}\)
  5. Simplify \(r(\sqrt{t-4})\) for the function \(r(t)=3-7t^2\text{.}\)
  6. Simplify \(y(t+5)-y(t-3)\) for the function \(y(t)=3t-16\text{.}\)
  7. Simplify \(w(x-2)+w(2-x)+2\) for the function \(w(x)=5-x\text{.}\)
  8. Simplify \(s(t-8)\) for the function \(s(t)=\frac{t+8}{t}\text{.}\)
  9. Simplify \(3u(2x)\) for the function \(u(x)=-x^2\text{.}\)
  10. Simplify \(\frac{1}{2}h(2t-7)-8\) for the function \(h(t)=8t-12\text{.}\)
Solution
  1. Simplify \(f(x-7)\) for the function \(f(x)=3x+12\text{.}\)
    \begin{align*} f(\highlight{x-7})\amp=3(\highlight{x-7})+12\\ \amp=3x-21+12\\ \amp=3x-9 \end{align*}
  2. Simplify \(g(x)+9\) for the function \(g(x)=14-7x\text{.}\)
    \begin{align*} g(x)\highlightr{+9}\amp=14-7x\highlightr{+9}\\ \amp=23-7x \end{align*}
  3. Simplify \(h(5-2t)\) for the function \(h(t)=\sqrt{3-t^2}\text{.}\)
    \begin{align*} h(\highlight{5-2t})\amp=\sqrt{3-(\highlight{5-2t})^2}\\ \amp=\sqrt{3-(5-2t)(5-2t)}\\ \amp=\sqrt{3-(25-20t+4t^2)}\\ \amp=\sqrt{3-25+20t-4t^2}\\ \amp=\sqrt{-4t^2+20t-22} \end{align*}
  4. Simplify \(k(x+4)+3\) for the function \(k(x)=2x^2-3\text{.}\)
    \begin{align*} k(\highlight{x+4})\highlightr{+3}\amp=2(\highlight{x+4})^2-3\highlightr{+3}\\ \amp=2(x+4)(x+4)\\ \amp=2(x^2+8x+16)\\ \amp=2x^2+16x+32 \end{align*}
  5. Simplify \(r(\sqrt{t-4})\) for the function \(r(t)=3-7t^2\text{.}\)
    \begin{align*} r(\highlight{\sqrt{t-4}})\amp=3-7(\highlight{\sqrt{t-4}})^2\\ \amp=3-7(t-4)\\ \amp=3-7t+28\\ \amp=31-7t \end{align*}
  6. Simplify \(y(t+5)-y(t-3)\) for the function \(y(t)=3t-16\text{.}\)
    \begin{align*} y(\highlight{t+5})-y(\highlightb{t-3})\amp=(3(\highlight{t+5})-16)-(3(\highlightb{t-3})-16)\\ \amp=3t+15-16-(3t-9-16)\\ \amp=3t-1-(3t-25)\\ \amp=3t-1-3t+25\\ \amp=24 \end{align*}
  7. Simplify \(w(x-2)+w(2-x)+2\) for the function \(w(x)=5-x\text{.}\)
    \begin{align*} w(\highlight{x-2})+w(\highlightb{2-x})\highlightr{+2}\amp=(5-(\highlight{x-2}))+(5-(\highlightb{2-x}))\highlightr{+2}\\ \amp=5-x+2+5-2+x+2\\ \amp=12 \end{align*}
  8. Simplify \(s(t-8)\) for the function \(s(t)=\frac{t+8}{t}\text{.}\)
    \begin{align*} s(\highlight{t-8})\amp=\frac{\highlight{t-8}+8}{\highlight{t-8}}\\ \amp=\frac{t}{t-8} \end{align*}
  9. Simplify \(3u(2x)\) for the function \(u(x)=-x^2\text{.}\)
    \begin{align*} \highlightg{3}u(\highlight{2x})\amp=\highlightg{3\cdot}-(\highlight{2x})^2\\ \amp=-3 \cdot 4x^2\\ \amp=-12x^2 \end{align*}
  10. Simplify \(\frac{1}{2}h(2t-7)-8\) for the function \(h(t)=8t-12\text{.}\)
    \begin{align*} \highlightg{\frac{1}{2}}h(\highlight{2t-7})\highlightr{-8}\amp=\highlightg{\frac{1}{2}}(8(\highlight{2t-7})-12)\highlightr{-8}\\ \amp=\frac{1}{2}(16t-56)-20\\ \amp=8t-28-20\\ \amp=8t-48 \end{align*}

Problem Set 1

Determine the solution set to each of the following equations based upon the function \(f\) shown in FigureĀ 1.15.12. State the solution set using both set-builder notation and interval notation.

  1. \(f(x) \lt 2\)
  2. \(f(x) \geq 2\)
  3. \(f(x) \lt -1\)
  4. \(f(x) \leq 5\)

plain text
Figure1.15.12\(y=f(x)\)

Problem Set 2

Determine the solution set to each of the following inequalities based upon the function \(g\) shown in FigureĀ 1.15.13. State the solution set using both set-builder notation and interval notation.

  1. \(g(x) \geq -2\)
  2. \(g(x) \leq 3\)
  3. \(g(x) \lt -6\)
  4. \(g(x) \gt -6\)

plain text
Figure1.15.13\(y=g(x)\)

Problem Set 3

Determine the solution set to each of the following inequalities based upon the function \(k\) shown in FigureĀ 1.15.14. State the solution set using both set-builder notation and interval notation.

  1. \(k(x) \geq 1\)
  2. \(k(x) \leq 4\)
  3. \(k(x) \gt 5\)
  4. \(k(x) \lt 6\)

plain text
Figure1.15.14\(y=k(x)\)

Solution

Problem Set 1

  1. The solution set is \(\{x \mid -2 \lt x \lt 0 \text{ or } 2 \lt x \lt 4\}\text{.}\)

    The solution set is \((-2,0) \cup (2,4)\text{.}\)

  2. The solution set is \(\{x \mid -4 \leq x \leq -2 \text{ or } 0 \leq x \leq 2 \text{ or } 4 \leq x \lt 5\}\text{.}\)

    The solution set is \([-4,-2] \cup [0,2] \cup [4,6)\text{.}\)

  3. The solution set is \(\{\}\text{.}\)

    The solution set is \(\emptyset\text{.}\)

  4. The solution set is \(\{x \mid -4 \leq x \lt 5\}\text{.}\)

    The solution set is \([-4,5)\text{.}\)

Problem Set 2

  1. The solution set is \(\{-2 \leq x \leq 3\}\text{.}\)

    The solution set is \([-2,3]\text{.}\)

  2. The solution set is \(\{x \mid -6 \lt x \lt 2 \text{ or } x \geq \frac{1}{2}\}\text{.}\)

    The solution set is \((-6,-2) \cup [\frac{1}{2},\infty)\text{.}\)

  3. The solution set is \(x \mid x \gt 5\}\text{.}\)

    The solution set is \((5,\infty)\text{.}\)

  4. The solution set is \(\{x \mid -6 \lt x \lt -4 \text{ or } -4 \lt x \lt 5\}\text{.}\)

    The solution set is \((-6,-4) \cup (-4,5)\text{.}\)

Problem Set 3

  1. The solution set is \(\{x \mid -1 \leq x \lt 0 \text{ or } 2 \lt x \leq 5\}\text{.}\)

    The solution set is \([-1,0) \cup (2,5]\text{.}\)

  2. The solution set is \(\{x \mid x \leq 0 \text{ or } x \geq 4\}\text{.}\)

    The solution set is \((-\infty,0] \cup [4,\infty)\text{.}\)

  3. The solution set is \(\{\}\text{.}\)

    The solution set is \(\emptyset\text{.}\)

  4. The solution set is \(\{x \mid x \leq 0 \text{ or } x \gt 2\}\text{.}\)

    The solution set is \((-\infty,0] \cup (2,\infty)\text{.}\)

Subsection1.15.3Workshop Materials (with short answers)